2016
DOI: 10.1016/j.ajpath.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Lymphedema Are Exacerbated and Prolonged by Neuropilin 2 Deficiency

Abstract: The vasculature influences the progression and resolution of tissue inflammation. Capillaries express vascular endothelial growth factor (VEGF) receptors, including neuropilins (NRPs), which regulate interstitial fluid flow. NRP2, a receptor of VEGFA and semaphorin (SEMA) 3F ligands, is expressed in the vascular and lymphatic endothelia. Previous studies have demonstrated that blocking VEGF receptor 2 attenuates VEGFA-induced vascular permeability. The inhibition of NRP2 was hypothesized to decrease vascular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Furthermore, members of these families are increasingly being appreciated as modulators of cell mediated immune responses, vascular disease and alloimmunity due to high expression levels of their receptors on leukocyte subsets [7073] and EC [7478]. Below, we wish to briefly discuss the class 3 semaphorin family (SEMA3) that have potential to regulate the alloimmune response [72,73,79].…”
Section: Class 3 Semaphorins As Novel Intragraft Factors With Potentimentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, members of these families are increasingly being appreciated as modulators of cell mediated immune responses, vascular disease and alloimmunity due to high expression levels of their receptors on leukocyte subsets [7073] and EC [7478]. Below, we wish to briefly discuss the class 3 semaphorin family (SEMA3) that have potential to regulate the alloimmune response [72,73,79].…”
Section: Class 3 Semaphorins As Novel Intragraft Factors With Potentimentioning
confidence: 99%
“…Over the past 10 years, several studies have identified SEMA3 receptors, including neuropilin (NRP)-1, NRP-2 and Plexin A family molecules on tumor cells suggesting that they function within the tumor microenvironment to limit cellular migration and growth [80,81,84,85]. Three members of the Class 3 family (SEMA3A, -3C and -3F) also bind NRP’s that are expressed on immune cell types including EC [7578,81], antigen presenting cells [86,87] and CD4 + T cells [70]. In general, ligation of the NRP receptor alone is not sufficient to elicit a signal, but serves as co-receptor to activate Plexin A family receptors that in turn elicit potent inhibitory signaling responses [88,89].…”
Section: Class 3 Semaphorins As Novel Intragraft Factors With Potentimentioning
confidence: 99%
See 1 more Smart Citation
“…Based on early transgenic mouse studies in this field, it was originally speculated that NRP1 is mainly expressed on arteries, arterioles and capillaries, whereas NRP2 is expressed on veins, venules and lymphatic vessels [9], [10]. However, subsequent studies have revealed that both NRPs are expressed in normal blood and lymphatic endothelial cells, and both play essential roles in forming blood and lymphatic vasculature networks [11], [12], [13]. Despite this, investigations into elucidating the roles of endothelial NRPs during angiogenesis have, for the most part, focused on NRP1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…This action of NRP-1 could be used in the future for the treatment of sepsis, since Gao et al were able to show that the NRP-1 agonist tuftsin improved sepsis survival through a reduction of Treg-induced immunosuppression [45,46]. Neuropilin 2 (NRP-2) protects the vascular barrier and increases lymphatic drainage during acute inflammation through endogenous Sema3F [47]. This demonstrates the growing recognition of the role of neuropilins in the regulation of acute inflammatory conditions.…”
Section: Ngps [ 4 7 3 _ T D $ D I F F ] Expressed In Endothelial Cellsmentioning
confidence: 89%